The Role of Social Media Engagement in Influencing Customer Loyalty in Saudi Banking Industry - Ajina, Ahmed Suhail (International Review of Management and Marketing, 2019)
Social media has gained significant popularity in the modern era, as people are spending an increasing amount of time over platforms like Facebook, Twitter and Instagram. This has instigated the organizations to amend their marketing communication techniques and to invest in the development of activities which may engage the customers. The aim of this research paper is to determine the role of social media engagement in influencing the customer loyalty from the perspective of the banking sector of Saudi Arabia. In order to ascertain this role, a combination of quantitative and qualitative methods has been employed in order to obtain relevant data and to come up with the conclusions. The regression analysis and the in-depth analysis of the qualitative data have established that the use of social media engagement has influenced the customers’ loyalty in the banking sector. Therefore, banks should further focus on the social media in enhancing the customers’ loyalty. Moreover, qualitative analysis suggests that customer loyalty gives strength to the financial position of the banks. Keywords: Social media; customers’ loyalty; Banking sector JEL Classifications: G21, L82 DOI: https://doi.org/10.32479/irmm.8060